Numerical Simulations of Carbon Dioxide Storage in Selected Geological Structures in North-Western Poland - Urych, Tomasz; Chećko, Jarosław; Magdziarczyk, Małgorzata; Smoliński, Adam (Frontiers in Energy Research, 2022)
In this study, dynamic simulation models of CO2 injection into saline aquifers of the Choszczno-Suliszewo structure located in north-western Poland were constructed for two scenarios with different injection rates. The injection rates of 1 Mt CO2/year and 2 Mt CO2/year were analysed for each of the injection wells. Changes in pressures characteristic for the sequestration process were analysed and the spatial distribution of free CO2 saturation in the structure and carbon dioxide dissolved in brine were presented in a graphical form. The observation time of changes occurring in the rock mass in the time interval up to 1000 years after completion of injection was assumed. During modelling of CO2 sequestration in Lower Jurassic aquifers in the Suliszewo model, the previously assumed CO2 injection rates were achieved for both injection scenarios. The observed pressure increase does not pose any threat to the Suliszewo structure tightness. The sequestration process was found to be highly effective due to the phenomenon of dissolution of CO2 in brine and resulting convection motion of brine enriched with carbon dioxide. Consequently, there is an increase in CO2 storage capacity and permanent long-term trapping of the injected carbon dioxide. The process of displacement of injected CO2 from the collector layers to the layers constituting the reservoir sealing was observed. This phenomenon takes place in the upper parts of the Choszczno structure and the main reason are the locally occurring worse technical parameters of seal layers in this area.